Resistance To Antiretroviral Therapy In People With HIV - Asryadin Asryadin; Nilasari Indah Yuniati; Lalu Addien Faqih Panjenengan; Baiq Trisna Satriana (Postgraduate, University of Mataram, 2023)
Human Immunodeficiency Virus (HIV) is a virus that damages the immune system, and has RNA genetic material which is converted by the reverse transcriptase enzyme into DNA. This research aims to determine the existence of resistance by identifying mutations related to drug resistance in HIV-1, especially in the genes encoding the PR and RT enzymes which are the targets of ARVs. This research uses the observational method. Research data analysis was carried out in the form of descriptive data analysis of the output of each formula based on the results of HIV measurements. This study contains a series of reviews that focus on the topic and incidence and possibility of HIV drug resistance (ART) in PLHIV/PLWHA. The main and important thing in detecting the possibility of resistance to ARV therapy is by examining the genotype and phenotype. Standardization between laboratories for drug resistance studies through the use of various methods, especially to identify mixed bases that cause estimated resistance mutations. Additionally, sequencing of protease, RT, and/or integrase is used to identify the clinical significance of DRM. There are two genetic mechanisms of NRTI resistance, namely: (1) discriminative mutations that activate RT to differentiate between the dideoxy-NRTI chain terminator and the cell's own dNTP; and (2) unblocking mutations that facilitate phosphorylytic excision of NRTI-triphosphate from viral DNA. Blocking mutations are also referred to as thymidine analogue mutations (TAMs). Â Â ARV resistance can be detected by examining the virus genotype which aims to determine the occurrence of mutations in one of the virus codons compared to ARV-sensitive wild type HIV-1 and by in vitro phenotyping, where this method takes quite a long time and is usually focused on finding a regimen new drug